KAJIAN TINGKAT DINAMIKA KLASTER DI JAWA TENGAH: - Lasmono Tri Sunaryanto; Ira Yumastuti (Badan Perencanaan Pembangunan, Penelitian dan Pengembangan Daerah Provinsi Jawa Tengah, 2011)
Small and medium enterprises (SMEs) need to be developed continuously as locally economic potential through the concept of clusters. SME cluster development methods are expected to integrate all development efforts so that maxized the results. This study wanted to evaluate the dynamics of SMEs clusters, particularly SMEs metal clusters in Tegal, Juwana and Pati. The research method used is descriptive research. The results showed that these three metal clusters under study are have not been so dynamic. Although for the metal clusters in Ceper and Juwana actually had been established quite along time ago, but in terms of its cluster development is basically still in 'early stage of cluster'. Their development stages is still at the stage of 'initial conditions', so no specialization et al. At this stage all existing SMEs in the cluster is still 'compete' with each other. In the aspect of cooperation, the three clusters still did not show the effort of cooperation and mutual support, as one of the core/essence of an evolving and dynamic clusters.